International Criminal Responsibility for ISIS Crimes against the Yazidi Component - Al-Jobory, Hakim (Journal of Legal Sciences, 2026)
This research examines international criminal responsibility for the crimes committed by the terrorist organization ISIS against the Yazidi community in light of the Rome Statute. Its importance stems from the gravity of the crimes committed, which have shaken the contemporary human conscience, including gross violations of human rights amounting to genocide and crimes against humanity. It also addresses the means of achieving national and international criminal justice. The research problem is represented by the following question: What is the criminal responsibility for the crimes committed by ISIS against the Yazidi community? And to what extent can they be characterized as international crimes committed in Iraq during the control of this terrorist organization? The research adopts the analytical-comparative-legal approach, by analyzing the relevant texts in the Rome Statute and comparing them with the documented facts of ISIS terrorist crimes against the Yazidis. This approach aims to determine the legal basis for international criminal accountability and highlight the challenges hindering its implementation in the Iraqi case. The research reached a number of conclusions and recommendations, most notably: The crimes committed by the terrorist organization ISIS meet the legal elements of an international crime, with their material and moral requirements. The material element is embodied in the acts of murder, enslavement, and forced displacement, while the moral element is represented by the specific criminal intent aimed at destroying a specific religious group. The research also concluded that the International Criminal Court (ICC) has, in principle, a specific mandate to consider these crimes. However, its practical application faces legal and political constraints resulting from Iraq’s failure to join the Rome Statute and the absence of a referral resolution from the UN Security Council. This necessitates Iraq’s accession to the Rome Statute or its acceptance of the ICC’s jurisdiction under Article 12/3 of the Statute. It also requires strengthening national efforts to document crimes and incorporates them into domestic legislation, ensuring criminal justice, and redress for victims, and consolidating the principle of non-impunity.